2020
DOI: 10.3389/fvets.2020.00448
|View full text |Cite
|
Sign up to set email alerts
|

Murine Thigh Microdialysis to Evaluate the Pharmacokinetic/Pharmacodynamic Integration of Cefquinome Against Actinobacillus pleuropneumoniae

Abstract: This study aimed to explore the application of microdialysis in pharmacokinetic (PK)/pharmacodynamic (PD) integration of cefquinome against Actinobacillus pleuropneumoniae. After the A. pleuropneumoniae population reached 10 6 CFU/thigh, the mice received 0.04, 0.16, 0.63, 2.5, and 10 mg/kg cefquinome by subcutaneous injection. Plasma samples were collected by retro-orbital puncture for 4 h, and thigh dialysate was obtained by microdialysis at a flow rate of 1.5 µL/min for 6 h for the PK study. For the PD expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Using an inhibitory Sigmoid E max model, the % f T > MIC values required for achieving bacterial growth inhibition as well as 1, 2 and 3 log 10 CFU/g reductions in the lung of infected pigs were 22.45, 28.86, 37.62 and 56.46%, respectively. The antimicrobial efficacy of cefquinome against A. pleuropneumoniae , as assessed using a neutropenic murine thigh infection model, showed that the % f T > MIC values required for achieving bacterial stasis and 1 and 2 log 10 CFU reductions were 31.61, 38.48 and 54.01%, respectively ( 33 ). In the neutropenic murine thigh infection model, the % f T > MIC values required to achieve the same antimicrobial efficacy are higher than those in the porcine experimental lung infection model.…”
Section: Discussionmentioning
confidence: 99%
“…Using an inhibitory Sigmoid E max model, the % f T > MIC values required for achieving bacterial growth inhibition as well as 1, 2 and 3 log 10 CFU/g reductions in the lung of infected pigs were 22.45, 28.86, 37.62 and 56.46%, respectively. The antimicrobial efficacy of cefquinome against A. pleuropneumoniae , as assessed using a neutropenic murine thigh infection model, showed that the % f T > MIC values required for achieving bacterial stasis and 1 and 2 log 10 CFU reductions were 31.61, 38.48 and 54.01%, respectively ( 33 ). In the neutropenic murine thigh infection model, the % f T > MIC values required to achieve the same antimicrobial efficacy are higher than those in the porcine experimental lung infection model.…”
Section: Discussionmentioning
confidence: 99%
“…The PKs of tilmicosin were determined in SPF chickens administered 15 mg/kg tilmicosin and we identified a T max of 1.50 h and t 1/2 of 20.10 h in plasma similar to other study results. For example, healthy chickens were administered 7.5 mg/kg tilmicosin orally resulted in a t 1/2 value of 22.67 h and a T max of 1 h (Zhang, Zhou, et al, 2020). Tilmicosin given orally at 15 mg/kg to broiler chickens resulted in a T max of 3 h and t 1/2 of 32 h (Dimitrova et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The in vitro recovery of tilmicosin was determined by dialysis and retrodialysis as previously described (Zhang, Zhou, et al, 2020). In brief, 500 ng/mL tilmicosin was provided at flow rates of 0.5, 1.0, 1.5 and 2.0 μL/min to ascertain the optimal perfusion rate.…”
Section: Methodsmentioning
confidence: 99%
“…The bacteria were grown as previously described ( 27 ) except that different media were used. Briefly, the bacterial were grown in supplemented TSB and TSA (see above).…”
Section: Methodsmentioning
confidence: 99%